The Relationship Between Maternal Knowledge About 1000 HPK With Nutritional Status in Children 0-24 Months - Pratiwi, Inka; Islaeli, Islaeli; Islamiyah, Islamiyah (Bantayang Omni Cendekia, 2024)
Background: Puuwatu Health Center is the puskesmas that has the highest nutritional status problems in 2022 according to (BB/U) compared to other puskesmas based on data from Puuwatu Health Center, the percentage of nutritional status of underweight (BB/Age) Puuwatu Health Center in 2022 is (39.08%). Objective: The purpose of this study was to determine the relationship between maternal knowledge about 1000 HPK with nutritional status in children 0-24 months in the working area of Puuwatu Health Center, Kendari City. Methods: This type of research is quantitative analytical research with a Cross-Sectional Study approach. Results: The analysis method of this study uses the Gamma Correlation Test. The results showed that there was a significant relationship between maternal knowledge and nutritional status in children 0-24 months with p = 0.000 which showed that there was a significant relationship between maternal knowledge and nutritional status in children and a correlation value of 0.788 showed a positive correlation with strong correlation strength. Conclusion: The conclusion of this study is that there is a relationship between maternal knowledge about 1000 HPK with nutritional status in children 0-24 months in the Puuwatu Health Center Working Area, Kendari City.